ANALISIS STRUKTUR PENGARUH BEBAN AKSIAL TERHADAP BALOK - G Giovani; Amir Mukhlis (Geuthèë Institute, Aceh, 2019)
This study focuses on the problem of critical compressive axial load. can be resist by the structure. The method used in this analysis is the finite element method. The basic concept of this method is that a continuous structure can be discretionally modeled into a simpler discrete structure, a discrete structure formed from a combination of elements whose behavior is expected to represent the behavior of a more complex structure. By using the finite element method can complete the analysis more simply. The final result of this study is to determine the value of the collapse load value of a structure, the displacement pattern that occurs, and the internal forces that occur with the finite element method approach. In the analysis of linear instability and in the analysis of non-linear instability for both prismatic and non-prismatic beams, there will be some differences in terms of working methods, critical load values, and values of displacement and internal forces.